Antecedents of Intention to Purchase Counterfeit Products: Case in Indonesian Consumers - Slamet Ahmadi; Harini Abrilia Setyawati; Santi Widhiastuti (Management Institute Faculty of Economics Universitas Andalas, 2021)
The objective of this study was to scrutinize the effect of materialism and novelty seeking on counterfeit purchase intention through attitudes. Data were collected from the youth in Indonesia, collected 177 respondents, processed using the PLS wrap. The analysis using path coefficient analysis indicated that novelty-seeking and attitude had an effect on buying interest counterfeit purchase intention through attitudes. On the other hand, materialism had no effect on attitudes and interests. Limited sampling frame may affect the general findings.